Foreign Direct Investment and Authoritarian Stability. (December 2016) - Bak, Daehee; Moon, Chungshik
This article examines how foreign direct investment (FDI) affects the likelihood of authoritarian leaders' political survival. We argue that FDI reduces the likelihood of experiencing political challenges from elites. We present two mechanisms for this claim. First, the host governments of authoritarian regimes can use FDI for long-term private good provision, so that FDI helps them to appease elite dissents and to buy off potential elite challengers. Second, FDI mitigates a commitment problem between elites and authoritarian leadership by creating an FDI-related distributional coalition, which in turn makes political defections costly to both parties. Our empirical tests using various two-stage estimators show that FDI significantly decreases the likelihood of elite-driven authoritarian leadership failure and coup attempt.